Genome-wide association study identifies candidate SNP markers and genes associated with low nitrogen tolerance in Brassica napus - Chen, Jingdong; Xie, Lingli; Hou, Xianfei; Yang, Rui; Liu, Jin; Dai, Xigang; Xue, Tianyuan; Yin, Shuai; Xu, Benbo; Zhang, Xuekun; Zeng, Changli; Xu, Jinsong (Frontiers in Plant Science, 2025)
Low nitrogen (LN) stress is a major limiting factor affecting crop growth and productivity. Understanding the genetic basis of LN tolerance is essential for improving nitrogen use efficiency in Brassica napus. A genome-wide association study (GWAS) was conducted on a panel of 275 B. napus accessions using a semi-automated hydroponic system to evaluate five seedling traits–leaf number (NL), shoot length (SL), root length (RL), shoot fresh weight (SFW), and root fresh weight (RFW)—under LN conditions. The system ensured environmental uniformity and high-throughput phenotyping. Significant phenotypic variation was observed across accessions, and correlation analysis suggested that RFW and SFW are key traits associated with LN tolerance. GWAS identified 71 significant SNPs, with 20 candidate genes located near these loci. Gene Ontology analysis revealed enrichment in nitrogen compound transport functions. Several genes such as NPF2.10, ATG4a, and AATL1 were implicated in nitrogen uptake, transport, remobilization, and stress adaptation. This study highlights the polygenic nature of LN tolerance and the importance of precise phenotyping in detecting stable genetic signals. The identified candidate genes are involved in nitrogen metabolism, autophagy, RNA processing, and amino acid transport, with transcriptomic evidence supporting the LN-responsive expression of BnaA09G0386000ZS. Comparative analysis with previous studies revealed unique SNP loci, likely due to differences in germplasm, nitrogen levels, and experimental design. These findings broaden our understanding of the genetic mechanisms underlying LN tolerance and provide promising targets for breeding B. napus varieties with improved nitrogen use efficiency.